Experience Implementing Ecosystem-based Adaptation in the Caribbean - Romany, Jaime (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Ms. Jaime Romany, Technical Officer, Inter-American Institute for Cooperation on Agriculture (IICA) - Trinidad & Tobago, Mr. Kent Coipel, Technical Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Dominica, Mr. Craig Thomas, National Specialist, Inter-American Institute for Cooperation on Agriculture (IICA) - Antigua & Barbuda